ORDER AND ANTI-ORDER IN OLIVINE I: STRUCTURAL RESPONSE TO TEMPERATURE - Heinemann R.; Kroll H.; Kirfel A.; Barbier B. (My University, 2006)
The crystal structure of Fe0.48Mg0.52[SiO4] olivine from the Boseti volcano, Ethiopia, has been investigated by single-crystal X-ray diffractometry at temperatures between 20 °C and 900 °C. For temperatures up to 600 °C, data were collected on crystals equilibrated at 600 °C. These data can therefore be assumed to reflect structural changes that are exclusively caused by thermal effects, whereas data collected between 600 °C and 900 °C carry additional information about the Fe2+,Mg equilibrium distribution. The in situ experiments at elevated temperatures were complemented by ambient temperature data collections on quenched crystals in order to check for possible Fe2+ and Mg redistributions during quenching. Such effects were found absent in crystals quenched from 800 °C or below. The derived temperature dependence of the Fe2+,Mg site distribution is In KD=0.4422(±0.0070)-140.0(±6.5)/T (K) according to which Fe2+ progressively anti-orders the M1 "octahedral" site as temperature is raised. A reverse ordering reaction at ≈650 °C leading to a strong segregation of Fe2+ into the other "octahedral" site, M2, as reported by Redfern et al. (2000), could not be detected. Both the and mean bond distances continously increase with temperature, exhibiting, however, a change in the increase rate at about 600 °C which conforms with an enrichment of the larger Fe2+ cation on the M1 site and its concomitant depletion on M2. In terms of bond lengths, the octahedral distortion of the M2 site is larger than that of M1. The opposite is true for the distortion defined in terms of the angles subtended at the cation site. Similar to the distances, the behavior of the distortion parameters both of which increase above 600 °C reflects the Fe2+,Mg anti-order. The relative magnitudes as well as the variation with temperature of both bond length and angular distortions can be rationalized considering the different geometrical environments of the M1 and M2 sites. With respect to isotrophic displacements parameters, U(M1)equiv is found larger than U(M2)equiv at all temperatures, also at variance with Redfern et al. (2000). © 2006 E. Schweizerbart'sche Verlagsbuchhandlung, D-70176 Stuttgart.
Keywords: ANTI-ORDER; DISTORTION; GEOSPEEDOMETRY; OLIVINE; ORDER; SOLID SOLUTION; THERMAL EXPANSION